Návrh motorového lože UL letounu s motorem B25 - Havlík, Marek; Marek Havlík (České vysoké učení technické v Praze, 2019)
Tato diplomová práce se zabývá návrhem konstrukce motorového lože ultralehkého letounu pro zástavbu motoru B25 značky MW Fly. První část práce je věnována analýze pohonné jednotky, rešerši používaných motorových loží a studii požadavků leteckých předpisů pro tento typ konstrukce. Druhá část práce se zaměřuje na stanovení zatížení na základě požadavků předpisů, návrh konstrukce motorového lože a pevnostní analýzu. Závěrem práce je provedena pevnostní kontrola, hmotový rozbor a návrh krytu motoru.

This master thesis deals with the design of the engine mount of an ultralight aircraft for instal-lation the MW Fly B25 engine. The first part of thesis is devoted to the analysis of the power unit, research of used engine mounts and study of the requirements of aviation regulations for this type of construction. The second part of the thesis focuses on the determination of loads based on requirements of regulations, design of the engine mount and strength analysis. At the end of the thesis is carried out strength check, mass analysis and design of the engine hood.
Engine mount design of UL aircraft with B25 engine
Keywords: motor; motorové lože; MWFly; ultralehky; analýza mkp; engine; engine mount; MWFly; ultralight; mkp analysis